Enterprise Architecture Model for a Rural Healthcare Service Facility in Java Indonesia - Lestari, Sri; Mustikawati, Novy; Bahri, Samsul (International Journal of Engineering and Technology, 2018)
The purpose of the enterprise architecture design is to align Technology Information with business for fulfilling the needs of the organization in the rural healthcare service facility sector. In this research, Enterprise Architecture design use Framework TOGAF Architecture Development Method. The research is focused in the rural healthcare service facility in Bandung, Indramayu and Brebes cities in Java Indonesia. The results provide enterprise architecture model for a rural healthcare service facility in Java Indonesia. This study is perhaps one of the first model for rural healthcare service facility in Java Indonesia.Â Â Â